Conducting an interview for research: what you should know. / Assoc Prof Dr Eley Suzana Kasim, Assoc Prof Dr Norlaila Md Zin and Dr Dalila Daud - Kasim, Eley Suzana; Md Zin, Norlaila; Daud, Dalila (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Interviews are a common method to collect data in qualitative studies. It involves acquiring data directly from interviewees thus making it possible for researchers to probe deeply into personal experiences, opinions, and feelings. In qualitative research, these interviewees are known as participants, unlike the term “respondents” commonly used in quantitative studies. It is usually useful to identify the different types of interviews which are unstructured, semi-structured and structured interviews.